2008
DOI: 10.1177/1077559507313461
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment Among Immigrant Chinese Families: Characteristics and Patterns of Placement

Abstract: This study examined the characteristics of child abuse among immigrant Chinese families in Los Angeles. The study also identified some of the critical variables contributing to the selection of one of two types of placement (in home or out of home) by the child protective services system. Data were obtained from 221 active Chinese case files maintained by the Asian Pacific Unit of the Los Angeles County Department of Children and Family Services. The extracted data were presented with logistic regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 16 publications
4
32
0
Order By: Relevance
“…14,15,31,32 There were no differences in maltreatment as a function of child gender in three studies, 14,31,32 but three others reported that being a boy constituted a risk factor 18,27,34 and another three reported that more girls from immigrant families were involved with CPS. 16,21,22 Two studies reported that children born outside the US and involved with CPS were more likely to be older than those born in the US and involved with CPS.…”
Section: Ontosystemic Risk Factors For Child Maltreatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…14,15,31,32 There were no differences in maltreatment as a function of child gender in three studies, 14,31,32 but three others reported that being a boy constituted a risk factor 18,27,34 and another three reported that more girls from immigrant families were involved with CPS. 16,21,22 Two studies reported that children born outside the US and involved with CPS were more likely to be older than those born in the US and involved with CPS.…”
Section: Ontosystemic Risk Factors For Child Maltreatmentmentioning
confidence: 99%
“…22,29,30 Of the 18 studies, 11 explored associations between country of origin and type of maltreatment (see Table 3 for details of these studies' results). The results generally show that children of immigrant families are most frequently reported for physical abuse 11,15,18,20,21,26,31,32 and to a lesser extent for physical neglect, 11,14 emotional/educational neglect 11,20 and sexual abuse 16,17,26 or to experience emotional abuse. 20,26 The authors explain that the higher rates of emotional abuse may be due to different parental practices and expectations regarding child rearing 16,32 or to the occurrence of intimate partner violence as reported by studies involving families of Mexican 26 and Korean origin.…”
mentioning
confidence: 94%
See 3 more Smart Citations